Metal-organic framework material based on scaffolding effect for regulating long afterglow luminescence characteristics and preparation method thereof

CN122917554APending Publication Date: 2026-10-16SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610685480.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

这些策略虽能通过改善电子结构、增强SOC、促进ISC等方式提升LAL性能,但普遍忽视了金属节点及MOF整体网络结构对发光行为的关键调控作用

Benefits of technology

[0027] (1) This invention successfully modulates the LAL properties of MOFs through an innovative network scaffold engineering strategy. This strategy utilizes the interaction between metal nodes and molecules, and by controlling the metal nodes and synthesis conditions, two MOFs with different topologies (MOF-SW21 and MOF-SW24) were constructed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A metal-organic framework material based on scaffold effect regulation long afterglow luminescence characteristics and a preparation method thereof, the material takes 2,3-pyridine dicarboxylic acid (H2L) as an organic ligand, takes Cd²⁺ as a metal node, and is constructed to obtain two MOF materials (MOF-SW21 and MOF-SW24) with different secondary structure units by regulating the metal node composition and synthesis conditions. By adjusting the metal node composition and the intermolecular interaction strength in the MOF framework, the phosphorescent lifetime is regulated to 20.70 ms to 139.85 ms, and the material has temperature-dependent, excitation-dependent and time-dependent multicolor LAL characteristics, which has important application value in the field of high-level anti-counterfeiting and encryption technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials technology, specifically relating to a MOF material with long afterglow luminescence performance controlled by network skeleton engineering, its preparation method and application, which is particularly suitable for high-security anti-counterfeiting and information encryption scenarios. Background Technology

[0002] As a special type of functional material that can continue to emit visible light after the excitation source is removed, LAL materials have shown broad application prospects in many fields such as advanced display, energy-saving lighting, high-security encryption and anti-counterfeiting, bioimaging and sensing due to their unique optical properties, and have become one of the current research hotspots in the field of functional materials.

[0003] MOFs are inorganic-organic hybrid materials assembled from metal nodes and organic ligands through coordination interactions. They possess significant advantages such as tunable network structure, diverse coordination environments, and strong framework rigidity. The periodic framework structure of MOFs can effectively restrict molecular vibrations and rotations, reduce non-radiative transition processes, and provide an ideal material platform for the regulation of long-afterglow luminescence performance, gradually becoming an important research direction for LAL materials.

[0004] Traditional strategies for regulating long-afterglow luminescence in MOFs are mostly ligand-centric, including ligand functionalization (introducing electron-donating or electron-withdrawing substituents onto ligands), mixed ligand strategies (introducing multiple ligands to construct multi-energy levels), and host-guest interaction strategies (using the MOF framework to immobilize guest molecules and regulate their arrangement and interactions). While these strategies can improve LAL performance by enhancing electronic structure, increasing SOC, and promoting ISC, they generally neglect the crucial regulatory role of metal nodes and the overall MOF network structure in luminescence behavior.

[0005] In fact, metal nodes, as the core components of MOFs, possess rich coordination properties. They can be precisely controlled to assemble into secondary structural units with different structures, thus significantly influencing the framework topology, intermolecular interactions, and electronic energy level distribution of MOFs. These secondary structural units, composed of metal nodes and their coordinating atoms, are the basic units of MOF structure and function. Changes in their morphology (such as mononuclear, binuclear, and metal chains) directly affect the material's luminescent properties. Therefore, developing network framework engineering strategies based on metal node control, and achieving precise control of the LAL performance of MOF materials by manipulating the morphology of SBUs and intermolecular interactions, is crucial for expanding the applications of MOFs in high-end anti-counterfeiting encryption, intelligent sensing, and other fields. It also represents a key problem that urgently needs to be solved in the current research field of MOF luminescent materials. Summary of the Invention

[0006] This invention aims to overcome the limitations of traditional MOF materials in terms of LAL regulation and single function. Using H2L as an organic ligand, and by adjusting the composition of metal nodes and synthesis conditions, two materials with different secondary structural units, MOF-SW21 and MOF-SW24, are constructed. Ultimately, the phosphorescence lifetime can be regulated from 20.70 ms to 139.85 ms, and multi-color LAL characteristics are dependent on temperature, excitation, and time. The material has thermal stability exceeding 300℃, providing high-performance functional materials and efficient preparation methods for high-end anti-counterfeiting and multi-dimensional information encryption.

[0007] The above-mentioned objective of this invention is achieved through the following technical solution:

[0008] A metal-organic framework material, MOF-SW21, and MOF-SW24, with long afterglow luminescence tunable by network skeleton engineering are provided. The phosphorescence lifetime of these two materials can be tuned in the range of 20.70 ms to 139.85 ms, and they have multicolor long afterglow luminescence characteristics that are temperature-dependent, excitation-dependent, and time-dependent.

[0009] Furthermore, using H2L as a ligand and CdCl2 as a metal salt, compounds MOF-SW21 and MOF-SW24 were prepared by hydrothermal reaction.

[0010] Furthermore, the preparation method of compound MOF-SW21 includes the following steps:

[0011] Step 1: Add ligand H2L to a polytetrafluoroethylene-lined stainless steel reaction vessel, along with the metal salt cadmium chloride, N,N-dimethylformamide, and methanol, and dissolve by sonication. The volume ratio of N,N-dimethylformamide to water is 1 ml:2 ml, and the molar ratio of H2L to cadmium chloride is 0.1 mmol:0.1 mmol.

[0012] Step 2: After complete dissolution, place the reaction vessel into the matching stainless steel high-temperature reactor, and then place the reactor into an electric heating drying oven. Heat the reactor from room temperature to 80-100 ℃ for 1-2 hours, maintain this temperature for 40-50 hours, and then cool it down to room temperature for 8-10 hours.

[0013] Step 3: After cooling to room temperature, the crystals were filtered and washed with methanol to obtain pure crystals of compound MOF-SW21.

[0014] Furthermore, in step 1, the molar ratio of H2L to cadmium chloride is 0.1 mmol:0.1 mmol, and the volume ratio of N,N-dimethylformamide to water is 1 ml:2 ml.

[0015] Furthermore, in step 2, the temperature is raised to 90°C for 2 hours, maintained at this temperature for 48 hours, and then cooled to room temperature for 10 hours.

[0016] Furthermore, the preparation method of the single crystal of the compound MOF-SW21 is as follows: A mixture of ligand H2L (16.7 mg, 0.1 mmol) and CdCl2 (18.3 mg, 0.1 mmol) is added to a 25 ml polytetrafluoroethylene-lined stainless steel reaction vessel, along with 1 ml of N,N-dimethylformamide and 2 ml of water. The mixture is then sonicated to dissolve it. After dissolution, it is placed in a matching stainless steel high-temperature reactor, which is then placed in an electrically heated drying oven and heated from room temperature to 90°C for 2 h. The reaction is carried out for 48 h, followed by cooling to room temperature for 10 h. Finally, the mixture is filtered and washed with methanol to obtain the single crystal of compound MOF-SW21.

[0017] Furthermore, the preparation method of compound MOF-SW24 includes the following steps:

[0018] Step 1: Add ligand H2L to a PTFE-lined stainless steel reaction vessel, along with the metal salt cadmium chloride, N,N-dimethylformamide, methanol, and water, and dissolve by sonication. The volume ratio of N,N-dimethylacetamide, methanol, and water is 1 ml:0.5 ml:0.5 ml, and the molar ratio of H2L to zinc chloride is 0.1 mmol:0.1 mmol.

[0019] Step 2: After complete dissolution, place the reaction vessel into the matching stainless steel high-temperature reactor, and then place the reactor into an electric heating drying oven. Heat the reactor from room temperature to 80-100 ℃ for 1-2 hours, maintain this temperature for 40-50 hours, and then cool it down to room temperature for 8-10 hours.

[0020] Step 3: After cooling to room temperature, the crystals were filtered and washed with methanol to obtain pure crystals of compound MOF-SW24.

[0021] Furthermore, in step 1, the molar ratio of H2L to cadmium chloride is 0.1 mmol:0.1 mmol, and the volume ratio of N,N-dimethylacetamide, methanol, and water is 1 ml:0.5 ml:0.5 ml.

[0022] Furthermore, in step 2, the temperature is raised to 90°C for 2 hours, maintained at this temperature for 48 hours, and then cooled to room temperature for 10 hours.

[0023] Furthermore, the preparation method of the single crystal of the compound MOF-SW24 is as follows: A mixture of ligand H2L (16.7 mg, 0.1 mmol) and CdCl2 (18.3 mg, 0.1 mmol) is added to a 25 ml polytetrafluoroethylene-lined stainless steel reaction vessel, along with 1 ml of N,N-dimethylformamide, 0.5 ml of methanol, and 0.5 ml of water. The mixture is then sonicated to dissolve it. After dissolution, it is placed in a matching stainless steel high-temperature reactor, which is then placed in an electrically heated drying oven and heated from room temperature to 90 °C for 2 h, reacted for 48 h, and then cooled to room temperature for 10 h. Finally, the mixture is filtered and washed with methanol to obtain the single crystal of compound MOF-SW24.

[0024] Furthermore, the preparation process of the 2,3-pyridinedicarboxylic acid (H2L) is as follows:

[0025] Powdered H2L was dissolved in ethanol and slowly evaporated to crystallize, yielding H2L single crystals. The crystals were found in the monoclinic P21 / c space group and showed intramolecular proton transfer from carboxyl hydrogen atoms to pyridine nitrogen atoms.

[0026] The present invention has the following beneficial effects:

[0027] (1) This invention successfully modulates the LAL properties of MOFs through an innovative network scaffold engineering strategy. This strategy utilizes the interaction between metal nodes and molecules, and by controlling the metal nodes and synthesis conditions, two MOFs with different topologies (MOF-SW21 and MOF-SW24) were constructed.

[0028] (2) The ligand-metal salt self-assembly system is controllable in synthesis, and the resulting MOF phase has high purity and stable structure, and has the potential for large-scale preparation and practical application.

[0029] (3) The material can realize advanced applications such as spatiotemporal dual-resolution anti-counterfeiting, temperature sensing, and ASCII character binary encoding, providing high-performance materials and technical solutions for advanced anti-counterfeiting and information storage. Attached Figure Description

[0030] Figure 1 A simplified 3D framework of MOF-SW21.

[0031] Figure 2 PXRD patterns of simulated and in-situ synthesized MOF-SW21 and MOF-SW24.

[0032] Figure 3 PXRD patterns of simulated and in-situ synthesized H2L.

[0033] Figure 4The infrared spectra of H2L, MOF-SW21, and MOF-SW24 are shown.

[0034] Figure 5 TGA curves for MOF-SW21 and MOF-SW24.

[0035] Figure 6 This is the solid-state UV-absorbing spectrum of H2L.

[0036] Figure 7 The solid-state UV-absorbing spectra of MOF-SW21 and MOF-SW24 are shown.

[0037] Figure 8 The room-temperature photoluminescence properties of H2L materials were studied: a) excitation spectra at different emission wavelengths; b) instantaneous emission spectra under different excitation conditions; c) fluorescence decay curves monitored at 440 nm wavelength; de) 1 ms delayed spectra under different excitation conditions; f) phosphorescence decay curves monitored at 500, 530 and 560 nm wavelengths.

[0038] Figure 9 The excitation spectra of MOF-SW21 and MOF-SW24 at different emission wavelengths at room temperature are shown.

[0039] Figure 10 The fluorescence decay curves of MOF-SW21 and MOF-SW24 at 470 nm are shown.

[0040] Figure 11 The emission spectra of MOF-SW21 and MOF-SW24 at room temperature with a delay of 1 millisecond were obtained under different excitation wavelengths.

[0041] Figure 12 Time-resolved emission spectra of MOF-SW21 and MOF-SW24 at different delay times under excitation at 360 nm and 450 nm.

[0042] Figure 13 The instantaneous emission spectra (λex = 360 nm) and delayed 1 ms spectra (λex = 360 nm and 450 nm) of MOF-SW21 and MOF-SW24 in air and vacuum at room temperature are shown.

[0043] Figure 14 The phosphorescence decay curves of MOF-SW21 and MOF-SW24 measured under air and vacuum conditions, and the variable-temperature phosphorescence decay curves monitored at wavelengths of 500 nm, 550 nm and 600 nm in the temperature range of 77 K to 300 K.

[0044] Figure 15The temperature-dependent lifetimes of MOF-SW21 and MOF-SW24 were monitored at wavelengths of 500, 550, and 600 nm within the temperature range of 77 to 300 K.

[0045] Figure 16 The instantaneous emission spectra (λex = 360 nm) and delayed 1 ms spectra (λex = 360 nm and 450 nm) of MOF-SW21 and MOF-SW24 in the temperature range of 77 K to 300 K, and their corresponding CIE coordinates are given.

[0046] Figure 17 The excitation spectra of MOF-SW21 and MOF-SW24 at different emission wavelengths under 77 K conditions are shown.

[0047] Figures 18-20 The LPL spectra of MOF-SW21 are obtained when it is irradiated at wavelengths of 275 nm, 311 nm, 365 nm, 385 nm, 405 nm and 450 nm at temperatures of 77 K, 100 K, 150 K, 200 K, 250 K and 300 K, respectively.

[0048] Figures 21-23 The LPL spectra of MOF-SW24 are obtained when it is irradiated at wavelengths of 275 nm, 311 nm, 365 nm, 385 nm, 405 nm and 450 nm at temperatures of 77 K, 100 K, 150 K, 200 K, 250 K and 300 K, respectively.

[0049] Figure 24 LPL images of MOF-SW21 and MOF-SW24 under irradiation at wavelengths of 275nm, 311nm, 365nm, 385nm, 405nm and 450nm in the temperature range of 77K to 300K.

[0050] Figure 25 a) LPL spectra of MOF-SW21 and MOF-SW24 immediately after irradiation with wavelengths of 275, 311, 365, 385, 405, and 450 nm at 77 K. b) LPL images of MOF-SW21 and MOF-SW24 at 77 K and 300 K.

[0051] Figure 26 Phosphorescence lifetime, bandgap, and spin-orbit coupling (SOC) of H2L, MOF-SW21, and MOF-SW24.

[0052] Figure 27 Specific application diagrams for MOF-SW21 and MOF-SW24. Detailed Implementation

[0053] The following examples will help to understand the present invention, but the examples do not limit the invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0054] Example 1: Preparation of organic ligand H2L

[0055] A ligand for MOFs, named 2,3-pyridinedicarboxylic acid (H2L), is a white solid powder with the following structure:

[0056]

[0057] A method for synthesizing ligands for MOFs, the specific steps of which are as follows:

[0058] Powdered H2L was dissolved in ethanol and slowly evaporated to crystallize, yielding H2L single crystals. The crystals were found in the monoclinic P21 / c space group and showed intramolecular proton transfer from carboxyl hydrogen atoms to pyridine nitrogen atoms.

[0059] Example 2: Synthesis of MOF-SW21 and MOF-SW24

[0060] (1) Synthesis of MOF-SW21.

[0061] A mixture of ligand H₂L (16.7 mg, 0.1 mmol) and CdCl₂ (18.3 mg, 0.1 mmol) was added to a 25 ml polytetrafluoroethylene-lined stainless steel reaction vessel, along with 1 ml of N,N-dimethylformamide and 2 ml of water. The mixture was then sonicated to dissolve the ligand. After dissolution, the solution was transferred to a matching stainless steel high-temperature reactor, which was then placed in an electrically heated drying oven and heated from room temperature to 90 °C for 48 h. The reaction was then cooled to room temperature after 10 h. Finally, the solution was filtered and washed with methanol to obtain single-crystal MOF-SW21.

[0062] (2) Synthesis of MOF-SW24.

[0063] A mixture of ligand H₂L (16.7 mg, 0.1 mmol) and CdCl₂ (18.3 mg, 0.1 mmol) was added to a 25 ml PTFE-lined stainless steel reaction vessel, along with 1 ml of N,N-dimethylformamide, 0.5 ml of methanol, and 0.5 ml of water. The mixture was then sonicated to dissolve the precipitate. After dissolution, the solution was transferred to a matching stainless steel high-temperature reactor, which was then placed in an electrically heated drying oven and heated from room temperature to 90 °C for 48 h. The reaction was then cooled to room temperature for 10 h. Finally, the solution was filtered and washed with methanol to obtain single-crystal MOF-SW24.

[0064] Example 3: Crystallographic data of MOF-SW21 and MOF-SW24.

[0065] Table 1. Crystal data for MOF-SW21 and MOF-SW24

[0066]

[0067] Example 4: Structural analysis of MOF-SW21 and MOF-SW24 crystals

[0068] Single-crystal X-ray diffraction analysis showed that both MOF-SW21 and MOF-SW24 used H2L as a ligand and interacted with Cd. 2+ The coordination assembly of metal nodes resulted in two different types of secondary structural units, which crystallized in different crystal systems and had distinct space groups, depending on the controlled synthesis conditions. MOF-SW21 crystallized in an orthorhombic crystal system with space group Pban, and its asymmetric unit contained one L... 2- ligand, 3 / 4 Cd 2+ The metal center contains ions and half a protonated dimethylamine molecule; two coordination environments exist: Cd1 and Cd2. Cd1 is a six-coordinate distorted octahedron, and Cd2 is an eight-coordinate polyhedron. Cd1 is located through μ - Bridging oxygen atoms to form a one-dimensional metal chain, with ligands in μ4-η 1 :η 1 :η 0 :η 1 :η 1 A 3D framework structure with one-dimensional channels is constructed by connecting the metal chains and Cd2 nodes. MOF-SW24 crystallizes in a triclinic system with space group P-1. The asymmetric unit cell contains two L... 2⁻ ligands, two Cd 2+The system consists of an ion, a coordinated water molecule, a lattice water molecule, and a lattice DMF molecule. Cd1 exhibits a six-coordinate structure with a distorted octahedral geometry: its coordination environment comprises four oxygen atoms and one nitrogen atom provided by four ligands, and one oxygen atom provided by a coordinated water molecule. In contrast, Cd2 exhibits a seven-coordinate structure, where L... 2⁻ The additional oxygen atom is embedded in its equatorial plane, forming a pentagonal bipyramidal coordination geometry. Among these coordinating atoms, two O3 atoms and two O5 atoms are observed to bridge Cd1 and Cd2 via μ2-O bonds, thus forming two distinct binuclear metal cluster units: Cd2O8N2 and Cd2O. 10 N2 (Fig. b). These two binuclear cluster units are further connected by O8 atoms along the ac plane in a μ2-O bridging mode, forming a one-dimensional metal chain (Fig. b). This scaffolding effect significantly limits the conformational flexibility of the ligands and helps to construct a stable two-dimensional framework together with the ligands (Fig. c). Intermolecular hydrogen bonds assemble these two-dimensional layers into a three-dimensional framework structure (Fig. d).

[0069] The experimentally measured PXRD peaks of H2L and MOFs are in high agreement with the simulated peaks, indicating that these materials were successfully prepared and have high phase purity. Figure 2 and 3 Thermogravimetric analysis (TGA) results showed that all MOFs exhibited excellent thermal stability, with stability temperatures exceeding 300°C. Figure 5 The weight loss of these MOFs below 200°C originates from the removal of lattice / coordination solvent molecules, consistent with the characteristics of solvent molecules present in their single-crystal structures. These characterization results collectively confirm the successful preparation of MOF materials and their excellent stability.

[0070] Example 5: Photophysical properties of MOF-SW21 and MOF-SW24

[0071] Solid-state UV-Vis absorption spectra of H2L and MOFs ( Figure 6-7 The results show that the absorption bands of MOFs are slightly wider than those of the ligands. This phenomenon can be attributed to the coordination-driven structural modifications within the MOF framework, which promote the diversity of electronic transition pathways. This structural effect is further demonstrated by room-temperature emission-dependent excitation spectroscopy. Figure 8-9 This structural effect was further confirmed.

[0072] Detailed experiments investigating the luminescence properties of H₂L have been completed. The excitation-dependent transient emission spectrum of H₂L shows an emission peak at approximately 440 nm when the excitation wavelength is below 400 nm. As the excitation wavelength extends above 400 nm, this peak gradually shifts towards 500 nm. Figure 8(b) This may originate from the phosphorescence effect of the ligand. Simultaneously, the peak at 440 nm exhibits a lifetime of 3.06 ns, confirming its fluorescence properties. Figure 8 c). Time-gated spectroscopy (1 ms delay) shows that as the excitation wavelength gradually increases, three emission peaks originating from the singlet triplet state and the aggregate triplet state appear at 500, 530, and 560 nm, respectively. Figure 8 As the excitation wavelength continues to increase, this phosphorescent emission gradually splits into a bimodal pattern, with maximum absorption peaks located at 500 nm and 560 nm, respectively. Notably, H₂L exhibits relatively long phosphorescent lifetimes at these wavelengths, measured to be 35.05 ms (500 nm), 27.75 ms (530 nm), and 27.95 ms (560 nm), respectively. Figure 8 f).

[0073] Researchers further investigated the luminescence properties and underlying mechanisms of MOFs. The steady-state emission peak positions of the obtained MOFs were similar to those of H2L, both exhibiting blue emission. Under 360 nm excitation, the delayed emission of MOFs showed a significant redshift to approximately 530 nm, consistent with the behavior of H2L; under 450 nm excitation, the delayed emission exhibited split double peaks or broad peaks, shifting towards the yellow-green region. Figure 9 Among them, MOF-SW21 and MOF-SW24 showed a more significant red shift and a yellowish luminescence. The short-lived emission in the blue region was attributed to fluorescence, with fluorescence lifetimes of 4.90 ns for MOF-SW21 and 3.95 ns for MOF-SW24. Figure 10 ).

[0074] Systematic studies show that the long-lifetime phosphorescence emission peaks of MOFs vary significantly with excitation wavelength, and the phosphorescence properties are inherited from the ligands. The optimal excitation-emission wavelengths are: MOF-SW21 (320 nm, 501 nm) and MOF-SW24 (320 nm, 500 nm), respectively. With increasing excitation wavelength, the emission peaks gradually redshift and decrease in intensity. MOF-SW21 elutes at 611 nm under 440 nm excitation, while MOF-SW24 elutes at 570 nm under 440 nm excitation. Time-resolved emission spectra (TRES) under 360 nm and 450 nm excitation confirm the broadening of the phosphorescence peaks and the existence of multiple electronic transition pathways. Although the emission signal at 600 nm is not significant, this indicates the presence of multiple electronic transition pathways. Figure 12 The results show that this type of MOF mainly emits light through ligand centers, and the phosphorescence performance can be finely regulated by the metal nodes through structural framework control.

[0075] To investigate the effect of oxygen on the luminescence properties of MOFs, the samples were subjected to vacuum treatment, and the transient and delayed emission spectra were measured under excitation at 360 nm and 450 nm. Figure 13 The results showed that the luminescence intensity of MOFs decreased in air, and the quenching effect was more significant in the gated spectrum; the phosphorescence lifetime was significantly prolonged after vacuum treatment. Figure 14 Furthermore, the phosphorescence efficiency and lifetime of MOFs are superior to those of the ligand H2L (Table S4-6). Low-temperature and vacuum treatments have similar effects, significantly extending the phosphorescence lifetime. Temperature-dependent phosphorescence decay curves and lifetime data from 77 K to 300 K validate this trend. Figure 14 (Table S5-6). Figure 15 It can be seen that the phosphorescence lifetime of MOF-SW24 is significantly higher than that of the other three materials, with a lifetime of 357.95 ms at the 500 nm emission peak at 77 K. The emission spectrum with a 1 ms delay at 77–300 K was measured under 450 nm excitation. Figure 16 The results show that as temperature decreases, the phosphorescence peak intensity at approximately 610 nm significantly increases, the emission peak redshifts overall and exhibits dual-emission phosphorescence characteristics, and low-temperature conformational limitation leads to the dominance of long-wavelength emission. Temperature-induced emission peak changes cause a significant shift in the phosphorescence color of MOFs, and the CIE coordinates change accordingly. For example, MOF-SW21 changes from 300 K (0.40, 0.43) to 77 K (0.54, 0.41), and MOF-SW24 shows a similar trend. Figure 17 As shown, the excitation-dependent emission spectrum at 77 K and the emission spectrum delayed by 1 ms indicate that long-wavelength excitation at low temperatures is more likely to induce long-wavelength phosphorescence emission, with a more significant redshift than at room temperature, consistent with the room temperature pattern but with a stronger effect.

[0076] Table 2: Lifetimes of different emission peaks of H2L and MOFs.

[0077]

[0078] Four MOFs with unique framework structures were synthesized by self-assembly of H₂L and different metal ions, exhibiting significant differences in luminescence behavior (Table 2). MOF-SW24 possessed the longest phosphorescence lifetime, attributed to abundant intramolecular and intermolecular non-covalent interactions, the rigid confinement effect of the chain-like framework, and the strongest heavy atom effect (SOC=241.6). Although MOF-SW21 had a chain-like structure, its high porosity and loose molecular packing led to enhanced ligand rotation and vibration, and intensified nonradiative transitions, resulting in the shortest phosphorescence lifetime, even shorter than that of the ligand H₂L. Experiments demonstrate that precise control of framework topology and intermolecular interactions can effectively regulate the room-temperature phosphorescence performance of MOFs.

[0079] The aforementioned long-lived MOFs exhibited significant long-afterglow luminescence behavior after the excitation source was removed. Researchers systematically tested their LPL spectra at excitation sources of 275 nm, 311 nm, 365 nm, 385 nm, 405 nm, and 450 nm, and temperatures of 77 K, 100 K, 150 K, 200 K, 250 K, and 300 K. Figure 18-23 The corresponding LPL images were acquired at 0.5 s intervals. Figure 24 The two-dimensional variable excitation spectra of the four MOFs at 77 K are compared with the LPL images at 77 K and 300 K, as shown in (). Figure 25 After excitation at 311 nm at room temperature, the material's LPL (Light Permeability) remains visible for over 5 seconds, with further extended afterglow time at low temperatures. Furthermore, the LPL color exhibits temperature-dependent, excitation-dependent, and time-dependent characteristics. Figure 26 As shown, decreasing temperature causes a blue shift in LPL color and an increase in intensity. For example, MOF-SW24, after being excited at 311 nm, is cyan-blue at 77 K and cyan-green at 300 K. The LPL color redshifts with increasing excitation wavelength and gradually redshifts with prolonged emission time. The multicolor, dynamically tunable, long-persistence characteristics of this type of MOF have significant application potential in high-end information encryption and anti-counterfeiting fields.

[0080] Example 6: Specific applications of MOF-SW21 and MOF-SW24 are as follows Figure 27 As shown;

[0081] (1) Multi-dimensional high-security information anti-counterfeiting and encryption: Spatiotemporal dual-resolution anti-counterfeiting module: The two and other MOF series materials are patterned to prepare customized modules (such as octagonal "88", as shown in Figures c and d). With 311 nm ultraviolet light as the excitation source, there is no information difference under ultraviolet light. After the light source is removed, the decay rate difference between MOF-SW21 short afterglow fast extinction and MOF-SW24 ultra-long afterglow continuous emission is used to achieve layered decryption: at a delay of 0.2 s, the afterglow of MOF-SW21 disappears first, revealing the first hidden pattern; at a delay of 1 s, combined with the long-term emission of MOF-SW24, the final core information is unlocked; and, dual-key ASCII character encoding encryption: with "311 nm ultraviolet light + time-dependent afterglow color" as the dual decryption key, the text invisible encryption is achieved by using the excitation / time-dependent emission redshift characteristics of the two (as shown in Figure f), realizing secondary encryption.

[0082] (2) Visualized multi-parameter sensing: 77 K~300 K low temperature visual sensing (as shown in Figure e): Utilizing the temperature-dependent emission redshift characteristics of both, MOF-SW24 is used as a high-precision detection unit and MOF-SW21 is used as an auxiliary verification unit. Through the synchronous change of emission color and peak intensity of the two, non-contact, visualized temperature detection in the low temperature range is achieved, and dual signal verification improves the sensing accuracy.

[0083] a) Theoretical model of LAL. b) LAL images of MOF-SW21 and MOF-SW22 under 365 nm wavelength illumination. c, d) Information processing system utilizing different LAL decay rates of metal-organic framework materials. e) Afterglow color patterns under temperature influence. f) Binary encoding of standard 8-bit ASCII characters.

[0084] Table S2. Bond lengths and angles (Å) for MOF-SW21.

[0085]

[0086]

[0087]

[0088] Table S3. Bond lengths and angles (Å) for MOF-SW24

[0089]

[0090]

[0091]

[0092]

[0093] Table S4. Phosphorescent lifetimes of H2L at 500 nm, 530 nm, and 560nm under room temperature in air.

[0094]

[0095] Table S5. Phosphorescent lifetimes of MOF-SW21 at 500 nm, 550 nm, and600 nm (RT in air / vacuum; different temperatures)。

[0096]

[0097] Table S6. Phosphorescent lifetimes of MOF-SW24 at 500 nm, 550 nm, and600 nm (RT in air / vacuum; different temperatures)

[0098]

[0099] Table S7. The S n / T n spin-orbit coupling matrix elements (SOCME, ξ) ofH2L and the four MOFs。

[0100]

[0101]

[0102] 。

Claims

1. A long-afterglow luminescent metal-organic framework material based on scaffolding effect-controlled network skeleton engineering, characterized in that, The material comprises two MOF compounds, MOF-SW21 and MOF-SW24, both of which use 2,3-pyridinedicarboxylic acid (H2L) as an organic ligand and Cd²⁺ as a metal node.

2. The metal-organic framework material according to claim 1, characterized in that... MOF-SW21 has a molecular formula containing L²⁻ ligands, Cd²⁺ ions, and protonated dimethylamine molecules, and crystallizes in the orthorhombic Pban space group; MOF-SW24 crystallizes in the triclinic P-1 space group, and its asymmetric units contain L²⁻ ligands, Cd²⁺ ions, coordinated water molecules, lattice water molecules, and lattice DMF molecules.

3. The method for preparing the metal-organic framework material according to claim 1, characterized in that, Using H2L as the organic ligand and a metal salt (CdCl2) as the metal node source, it is prepared via a hydrothermal reaction, specifically including the following steps: Step 1: Add the organic ligand H2L and the metal salt to a 25ml stainless steel reaction vessel lined with polytetrafluoroethylene in a 1:1 ratio, add solvent, and sonicate to dissolve. Step 2: After complete dissolution, place the reaction vessel into the matching stainless steel high-temperature reactor, and then place the reactor into an electric heating drying oven. Heat the reactor from room temperature to 80-100 ℃ for 1-2 hours, maintain this temperature for 40-50 hours, and then cool it down to room temperature for 8-10 hours. Step 3: Filter the product and wash it 2-3 times with methanol solvent to obtain the target MOF material.

4. The preparation method according to claim 3, characterized in that, In the preparation of MOF-SW21, the molar ratio of H2L to cadmium chloride was 1:1, the solvent was a mixture of 1 mL N,N-dimethylformamide and 2 mL methanol, and the product yield was 65%.

5. The preparation method according to claim 3, characterized in that, In the preparation of MOF-SW24, the molar ratio of H2L to cadmium chloride was 1:1, the solvent was a mixture of 1 mL N,N-dimethylformamide, 0.5 mL methanol and 0.5 mL water, and the product yield was 65%.

6. The preparation method according to claim 3, characterized in that, The organic ligand H2L is prepared by dissolving powdered H2L in ethanol, slowly evaporating and crystallizing to obtain H2L single crystals, which crystallize in the monoclinic P21 / c space group.

7. An application of the metal-organic framework material according to claim 1, characterized in that, The material is used in the preparation of advanced anti-counterfeiting labels, multi-dimensional information encryption, or temperature sensing, and can achieve information encryption and decryption by adjusting the excitation wavelength, temperature, or delay time.